Manufacturing of sintered lightweight aggregate using high-carbon fly ash and its effect on the mechanical properties and microstructure of concrete - Yiu Lo, Tommy; Cui, Hongzhi; Memon, Shazim Ali; Noguchi, Takafumi (Journal of Cleaner Production, 2016)
Fly ash is the largest source of industrial solid waste in China. Fly ash with its high content of unburned carbon has to be discarded in landfills and cause environmental problem. To reduce the environmental impacts, lightweight aggregate (LWA) was manufactured utilizing high-carbon fly ash (HCFA) (loss on ignition, LOI = ∼16.3%). Trial tests were conducted on high-carbon fly ash lightweight aggregate (HCFA-LWA) in a laboratory electric furnace and in a manufacturer's batch furnace. A new temperature profile was proposed for the HCFA-LWA sintering process in which carbon served as a partial fuel substitute during the burning period, which can decrease the sintering period in the sintering stage of the LWA and save energy.
Keywords: Concrete; High-carbon fly ash; Lightweight aggregate; mechanical properties; Microstructure; Temperature regime; Research Subject Categories::TECHNOLOGY::Engineering physics